Translating New York : the city's languages in Iberian literatures - Galasso, Regina (Contemporary Hispanic and Lusophone cultures, 2018)
The pre-publication version of Translating New York was awarded the 2017 Northeast Modern Language Association Book Award for the best unpublished book-length manuscript on modern language literature. Drawing from several genres, Translating New York recovers cultural narratives occluded by single linguistic or national literary histories, and proposes that reading these texts through the lens of translation unveils new pathways of cultural circulation and influence. Galasso argues that contact with New York ignited a heightened sensitivity towards language, garnering literary achievement and a.